Peranan Pendidikan Agama Kristen Terhadap Kebebasan Media Massa Terhadap Pendidikan Agama Kristen - Daud Marsahata Simamora (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
This article examines the role of Christian religious education in influencing mass media freedom and its impact on Christian religious education itself. In the context of globalization and digitalization, mass media has become the main means of disseminating information and religious values. Christian religious education functions to equip students with a critical understanding of media content, so that they are able to sort and understand religious teachings in dealing with various emerging perspectives. This research highlights the relationship between Christian religious education and the influence of mass media on the formation of the religious identity of the younger generation. The findings show that good Christian religious education can strengthen students' freedom of thought, help them to integrate Christian values ​​in everyday life, and create a deeper awareness of the influence of the media. Thus, synergy between religious education and mass media is very important to promote a holistic understanding of Christian teachings in modern society.